Alcoholism among the priests of the Đakovo-Osijek Archdiocese - Šota, Stanislav (Array, 2021)
In many countries today, alcoholism is becoming an increasingly common problem, the number of alcoholics is increasing, and the disease occurs in all professions and occupations. Therefore, it is important to talk about the increasing presence of alcoholism not only among lay believers but also among the clergy of the Catholic Church. The aim of this paper is to point out the causes of alcohol addiction and the consequences of alcoholism on the life and work of priests from the area of the Đakovo-Osijek Archdiocese. Based on the results of qualitative-quantitative research conducted using a survey questionnaire (9 priests), sampled using the "snowball" technique, this paper will, for the first time, talk about a problem that has not been discussed in the Croatian scientific community. The conducted research points to stressful events, loneliness, and mis-understanding of superiors and the environment as the main causes of alcoholism among priests.